2015
DOI: 10.1038/srep08520
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for PPARγ transactivation by endocrine-disrupting organotin compounds

Abstract: Organotin compounds such as triphenyltin (TPT) and tributyltin (TBT) act as endocrine disruptors through the peroxisome proliferator–activated receptor γ (PPARγ) signaling pathway. We recently found that TPT is a particularly strong agonist of PPARγ. To elucidate the mechanism underlying organotin-dependent PPARγ activation, we here analyzed the interactions of PPARγ ligand-binding domain (LBD) with TPT and TBT by using X-ray crystallography and mass spectroscopy in conjunction with cell-based activity assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 28 publications
2
74
0
2
Order By: Relevance
“…TBT-exposure during puberty led to weight gain, insulin resistance, increased leptin, and fatty liver in male mice 42 . Structural studies confirmed that TBT possesses nanomolar binding affinity for RXR, whereas, a related organotin, triphenyltin, bound both PPARγ and RXRα avidly 43-44 . Organotins still remain the only obesogens for which a molecular mechanism has been delineated.…”
Section: A Brief History Of Obesogensmentioning
confidence: 86%
“…TBT-exposure during puberty led to weight gain, insulin resistance, increased leptin, and fatty liver in male mice 42 . Structural studies confirmed that TBT possesses nanomolar binding affinity for RXR, whereas, a related organotin, triphenyltin, bound both PPARγ and RXRα avidly 43-44 . Organotins still remain the only obesogens for which a molecular mechanism has been delineated.…”
Section: A Brief History Of Obesogensmentioning
confidence: 86%
“…We previously demonstrated that specific binding of organotin compounds is achieved through non-covalent ionic interactions between the tin atom and the sulfur atom of C432 of hRXRα or C285 of hPPARγ. 22,23) However, the either C432 mutation of hRXRα or C285 mutation of hPPARγ did not result in significant effect of the ligand activity of TPAs and TPBi, for each receptor (Figs. 4, 6).…”
Section: Discussionmentioning
confidence: 92%
“…The resulting mutant constructs are designated pBK-CMV-GAL4-hRXRαC432A, and pM-PPARγC285A, respectively. 22,23) The LBDs of hRXRα (amino acids 201-462) were subcloned into pGEX-4T (GE Healthcare Life Sciences, Buckinghamshire, U.K.). 20) The DNA sequence encoding hPPARγ was cloned into pGEX-2T (GE Healthcare Life Sciences).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations